A Sociophonetic Investigation of Standard British English Connected Speech Processes in Nigerian English (2014)
Connected speech processes (CSPs) account for sound modifications and simplifications in speech, while sociophonetics emphasises correlation between speech forms and social factors. Existing studies merely identified some CSPs that characterise Nigerian English (NE); studies that measure speakers' proximity to Standard British English (SBE) connected speech, especially in relation to social variation, are scarce. This study, therefore, investigated the incidence of assimilation, elision and liaison processes of SBE connected speech in NE with consideration for the region, gender and age of speakers. This is with a view to determining the level of NE speakers' approximation to or deviation from SBE. The study adopted generative phonology to explain NE speakers' application of or deviation from the SBE rules, and variability concept to show the correlation between CSPs and social factors. The participants, who ranged between ages 18-65, were 180 male and 180 female NE speakers with a minimum of 2-3 years post-secondary education. They were drawn, through stratified and purposive techniques, from four regions in Nigeria: north (120), west (80), east (80) and south-south (80). All participants produced semi-spontaneous speeches (SSS), containing 31 utterances and a short passage, into digital recording devices and filled 360 copies of a structured questionnaire. Two educated native speakers served as control. The recordings were transcribed and the scores analysed, using percentages, MANOVA and Bonferroni's Post-hoc test. Portions of the SSS of eight participants (representing the social variables) and one native speaker were analysed acoustically, using PRAAT speech analyser (version 5120). The overall incidence of the CSPs (assimilation, elision and liaison) of SBE for all categories of participants indicated 43.2% approximation and 56.8% deviation. However, incidence of each process varied. Three assimilation variants- regressive devoicing (99.2%), progressive devoicing (65.1%) and nasal assimilation (63.5%)- showed significant approximation to SBE, while four variants- progressive voicing (21.2%), voiceless alveolar stop assimilation (47.6%), voiced alveolar stop assimilation (3.2%) and yod coalescence (6.2%)- deviated significantly. Consonant elision, in all contexts, occurred significantly (61.5%), while the incidence of liaisonlinking /r/ (8.1%) and intrusive /r/ (2.9%)- was extremely low. The speech waveforms, formants structure and voicing bars on the participants' spectrograms, in most cases, displayed considerable deviation from SBE. In terms of social variation, the combined dependent variable (assimilation, elision and liaison) was significantly affected by gender (Pillai's Trace=0.07,F(3,342)=8.12,p<0.05,η2=0.07) and region (Pillai's Trace=0.11,F(9,1032)=4.29,p<0.05,η2=0.04), but not by age or their interactions. Gender had significant effect on elision F(1,344)=22.21;p<0.01,η2=0.06): males had higher mean performance (M=9.91;SD=2.84) than females (M=8.55;SD=2.58). Region was found to be significant in liaison F(3,344)=8.14;p<0.01,η2=0.07): Eastern participants (M=1.38;SD=1.44) had the highest mean score, followed by South-South (M=1.10;SD=1.22), Western (M=1.05;SD=1.16) and Northern participants (M=0.57;SD=0.94). The Bonferroni's Post-hoc results indicated that only Eastern and Northern participants differed significantly from each other. Nigerian English speakers' mastery of Standard British English connected speech processes, irrespective of gender and regional variation, manifested, overall, more deviation from than approximation to SBE. This suggests Nigerian English speakers' relatively low level of competence in Standard British English connected speech processes, and has implications for intelligibility